Life within and life of a mining town: the historical geography of Western Australia’s first iron ore town - Davies, Amanda; Oliver, Bobbie (Routledge, 2017)
Small resource-dependent towns are particularly vulnerable to economic decline as they often have limited internal capacity to develop alternative economic functions. This paper presents the story of the development, decline and adaptation of a small resource-dependent town. Recognising that the processes informing the development trajectories of resource communities are diverse, temporally embedded and multi-scalar, this paper argues that the everyday activities of the residents inform the life of resource towns, and, moreover, lives within these places. The paper presents the story of Wundowie—Western Australia’s first iron ore town. This is interwoven with the story of the Kowalski family—a migrant family whose history, typical of many of the town’s original residents, made the town.